Diffusion of Innovations in Health Service Organisations : a Systematic Literature Review. - Greenhalgh, Trisha (Studies in urban and social change., 2008)
This is a systematic review on how innovations in health service practice and organisation can be disseminated and implemented. This is an academic text, originally commissioned by the Department of Health from University College London and University of Surrey, using a variety of research methods. The results of the review are discussed in detail in separate chapters covering particular innovations and the relevant contexts. The book is intended as a resource for health care researchers and academics.